Perempuan Pemanggang Ikan Laut di Desa Kriyan: Upaya Perempuan Meningkatkan Kesejahteraan Keluarga melalui Ekonomi Informal - Dinda Pristi Senta; Moh Yasir Alimi (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This article examines the socio-economic role of women who grill sea fish in Kriyan Village, Jepara to improve their family's welfare. The formulation of the problem raised in this study is how is the socio-economic background of women who grill sea fish in Kriyan Village, the socio-economic role of women who grill sea fish in improving family welfare, and the impact of grilling sea fish on family welfare. This research was conducted in Kriyan Village, Kalinyamatan District, Jepara, using a qualitative approach, this study involved active women who work as sea fish grillers. Data collection was carried out by means of interviews, observations, and documentation, then analyzed descriptively. The results of the study indicate that the involvement of women in this sea fish grilling business makes a significant contribution to increasing family income and strengthening women's social position in society. The role of women who grill sea fish in Kriyan Village is very strategic in strengthening the family economy and encouraging social development in society and becoming agents of social change for the struggle for gender equality in society.